Os sitiantes de Córrego das Pedras (MT): trajetórias de vida e memórias da terra de trabalho - Pereira Filho, José (Universidade Federal de São Carlos, 2019)
The present work titled: "THE BESIEGERS OF ‘CÓRREGO DAS PEDRAS’ (MT): life trajectories and memories of the work land", aims to understand the social dynamics regarding the strategies and forms of survival of families living in minis, small and medium rural properties, called small farms, in the community of Córrego das Pedras, in the municipality of Tangará da Serra (MT), understanding the land as a means to guarantee, through the work of the besieging families that reside and work in it, the production and reproduction of a life. It is a qualitative research, having as methodology oral history and memory, in which I used, mainly, the direct observations and the interviews of open and semi-structured script as methodological resources for data generation. I also used questionnaires and documentary surveys as complementary procedures. The analyzes are based on the perception of the life trajectory of migrant families from Minas Gerais and São Paulo who migrated with their habits, customs and traditions. The besiegers did not surrender to the process of expropriation of their lands, own of the regions where the modern capitalist agriculture establishes and advances. They subsisted in time, in their fractions of land, producing and reproducing their own dynamics of life and generating culture, in symbiosis between modernity and tradition. I point to the premise that the forms of production of material life constructed over time, - these heterogeneous forms, combined with the production and reproduction of the caipira culture, manifest in the writings of Candido (1982), perceived in the festivals, in the confraternizations, in cooking and religious practices - were decisive for the production and reproduction of a way of life and the permanence of the families in their places. I made reference to a daily resistance, produced daily in the struggle of the families to remain in their portions of land and to produce their own material existence and of their families, in front of the agribusiness advances in the region. The conquest and permanence in their lands also ended up constituting a resistance to the development model proposed for the State and region, with a predominance of rural estates, now transformed into modern agribusiness rural enterprises, focused on the production of monocultures such as: soybeans, corn, cotton and the extensive breeding of cattle for slaughter. While the agribusiness model turns to supply the capitalist market, the besiegers' experiences return to the production and reproduction of rural life. I emphasize the role played by women in the course of the entire production and reproduction of family life trajectory. Historically, partners of their husbands, therefore, protagonists of the trajectory of resistance. No more nor less than men, but women of struggle and in struggle. In the ways of the research, I was able to look to the future, especially from the children, adolescents and young people, using a dialogical relationship, through drawings, that showed the sensitivity and the affection towards the land. The diverse and plural rural world lives and reproduces, looking to the future, establishing new forms of relationship of men and women between themselves and with the land.
The besiegers of community of Córrego das Pedras: life trajectories and memories of workland
Keywords: Ruralidade; Sitiantes; Memórias; Trajetórias; Cultura; Resistência; Mato Grosso; Rurality; Besiegers; Memory; Trajectory; Culture; Resistance; CIENCIAS HUMANAS::SOCIOLOGIA